Distribution and habitat preference of polar cod (Boreogadus saida) in the Bering and Chukchi Seas inferred from species-specific detection of environmental DNA - Tatsuya Kawakami; Aya Yamazaki; Aya Yamazaki; Hai-Chao Jiang; Hiromichi Ueno; Akihide Kasai (Frontiers in Marine Science, 2023)
Ongoing warming and sea-ice reductions in the Arctic can seriously impact cold-water species, such as polar cod (Boreogadus saida), necessitating biomonitoring to reveal the ecological consequences. Recent methodological advancements in environmental DNA (eDNA) techniques have increased our ability to conduct ecological monitoring at various locations, including the Arctic. This study aimed to provide an overview of the distribution of polar cod across the Bering and Chukchi Seas by employing species-specific detection of eDNA. First, we successfully developed novel species-specific qPCR assay targeting the mitochondrial D-loop region, which exclusively amplifies eDNA derived from polar cod. Subsequently, polar cod eDNA was detected using the assay from the samples that we collected latitudinally across the study area during the open-water season. Polar cod eDNA was primarily detected in the surface water from the central Chukchi Sea shelf and the northernmost observation line (75°N), which was located on the shelf slope, off the Point Barrow, and in the marginal ice zone. In contrast, only trace amounts of eDNA were detected in the Bering Sea. This pattern corresponded well with the distribution of water masses classified based on environmental conditions. The detection of eDNA in surface water was clearly limited to cold (-1 to 5°C) and low salinity (25–32) water, whereas it was detected in a higher salinity range (32–34) in the middle and bottom layers. These findings are consistent with current knowledge about the distribution and habitat of the polar cod, suggesting that eDNA can be regarded as a reliable tool to replace or supplement conventional methods. Incorporating eDNA techniques into large-scale oceanographic surveys can improve the spatial and temporal resolution of fish species detection with a reasonable sampling effort and will facilitate the continuous monitoring of Arctic ecosystems.